2014
DOI: 10.2478/s13382-014-0288-2
|View full text |Cite
|
Sign up to set email alerts
|

Occupational concerns associated with regular use of microscope

Abstract: Objectives: Microscope work can be strenuous both to the visual system and the musculoskeletal system. Lack of awareness or indifference towards health issues may result in microscope users becoming victim to many occupational hazards. Our objective was to understand the occupational problems associated with regular use of microscope, awareness regarding the hazards, attitude and practice of microscope users towards the problems and preventive strategies. Material and Methods: a questionnaire based survey done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 12 publications
1
14
2
3
Order By: Relevance
“…Out of the total 132, 80 were males and 52 were females [ [8]. Jain G and Shetty P observed that 62% of the participants were affected by MSDs [9]. In our study we found that General Pathologists and Microbiologists had similar results.…”
Section: Results and Observationssupporting
confidence: 80%
“…Out of the total 132, 80 were males and 52 were females [ [8]. Jain G and Shetty P observed that 62% of the participants were affected by MSDs [9]. In our study we found that General Pathologists and Microbiologists had similar results.…”
Section: Results and Observationssupporting
confidence: 80%
“…Additionally, physical therapists and allied health professions who work in laboratories work with prolonged use of medical devices such as microscopes and sonographs. WMSDs among physical therapists were mainly in the lower back (46.5 percent), shoulder (45.2 percent) and neck (44.9 percent) [20], while the overall WMSDs among other allied health professions such as microscope workers, pathologists and radiologic technologists were 62, 76 and 88.9 percent, respectively [21][22][23]. Among nurses, the overall prevalence of WMSDs was about 55.6-91.7 percent.…”
Section: Resultsmentioning
confidence: 99%
“…%44'ü mikroskopta uzun süre çalışmaktan sonra kendilerini stres altında hissettiklerini belirtmişlerdir. Mikroskopla çalışanlarda en çok görülen iş kaynaklı rahatsızlıklar boyun ve sırtta oluşan kas-iskelet problemleri, göz yorgunluğu, ametropinin şiddetlenmesi, baş ağrısı, çalışma anında veya sonrasındaki anksiyete olarak sıralanmaktadır (Jain and Shetty, 2014 Mikrobiyoloji laboratuvarlarında farklı işlemler için biyogüvenlik kabini kullanılmaktadır (Şekil 4).Laboratuvar çalışanı,biyogüvenlik kabini ile çalışırken yanlış çalışma pozisyonu, ayak ve bilek destek elemanlarının bulunmayışı, kabin içinde gereksiz istifleme yapılması, ayak ve bacaklar için boşluk bulunmaması, uygunsuz sandalye kullanımı, çalışma yüzeyine temas eden kol ve bilek, kabinde yapılan uzun süreli çalışma kas-iskelet sistemi problemlerinin ortaya çıkmasına neden olmaktadır. Çalışan özellikle boyun, omuz, sırt, ayak, bacak, bilek ve kollarda ağrıların oluşması gibi olumsuz birçok etkene maruz kalmaktadır.…”
Section: Elektromiyografikunclassified